Pengaruh Worklife Balance dan Kompensasi Terhadap Kinerja Karyawan Pada Bank di Kecamatan Bengkalis - Anggraini, Marselina (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
This study aimed to determine how much influence worklife balance has on employee performance, how much influence compensation has on employee performance and how much influence worklife balance and compensation have on employee performance. This research is a quantitative study with a research instrument test approach, classical assumption test, multiple linear regression, hypothesis testing, and determination coefficient test (R2) to measure the relationship between variables. Research data obtained from distributing questionnaires to customer service and bank tellers in Bengkalis. The data collection technique used was a questionnaire. The results showed that the worklife balance variable had a significant effect on employee performance at the Bank in Bengkalis, the compensation variable had an insignificant effect on employee performance at the Bank in Bengkalis, and the worklife balance and compensation variables simultaneously or together had a significant effect on employee performance at the Bank in Bengkalis.Â Keywords: Worklife Balance, Compensation, Employee Performance, Bank Employees